Grounding the prophet Muhammad eating manners: prophetic food as a local food literacy movement in elementary schools - Nuraly Masum Aprily; Nana Supriatna; Mubiar Agustin; Ernawulan Syaodih (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2025)
The low level of local food literacy among elementary school students, influenced by globalization and the dominance of instant food consumption, requires a more holistic educational approach. This article aims to formulate the conceptual framework of Prophetic Food as a literacy model grounded in the eating manners of Prophet Muhammad. A systematic literature review was conducted, screening 173 articles and narrowing them to 15 relevant studies using explicit inclusion and exclusion criteria. The analysis revealed three major themes: (1) the importance of school-based nutrition interventions in shaping healthy eating behaviors; (2) the increasing emphasis on halalan thoyyiban principles in food consumption; and (3) the relevance of local food systems for sustainability and cultural identity. Integrating the Prophet’s eating etiquette—simplicity, cleanliness, moderation, and communal sharing—this study proposes Prophetic Food as a framework built on five prophetic values: al-‘adl (justice), al-thohārah (cleanliness), qona’ah (moderation), al-karīm (generosity), and al-akhlaq al-karīmah (noble character). The findings conclude that Prophetic Food expands food literacy beyond nutrition toward ethical, spiritual, and sustainability-oriented education. Practical implications include project-based school activities, such as communal meals following prophetic traditions, and policy recommendations for integrating prophetic food literacy into the national curriculum.